Analisis Perubahan Tutupan Lahan terhadap Suhu Permukaan Kecamatan Jati Agung, Kabupaten Lampung Selatan - Kurniawan, Rizko Dwi; Franjaya, Eduwin Eko; Ali, Muhammad Saddam (Jurnal Lanskap Indonesia, 2026)
The population in Jati Agung District increased from 2013 to 110,180 people to 128,604 people in 2022 with a population density of 782 people/km². This increase in population will have an impact on changes in land cover and surface temperature. This has adverse effects such as increased energy consumption, increased air pollution and health risks. Therefore, this study aims to determine changes of land cover and surface temperature in Jati Agung District within the year 2013-2022. The methods used in this study are guided classification and conversion of digital number values into surface temperature. Jati Agung District within 9 years (2013-2022) experienced the largest land cover change in vegetation areas. The area of changes that occurred were built-up lands increased by 1569.21 ha, open lands decreased by 150.86 ha, water surfaces decreased by 150.36 ha, and vegetation areas decreased by 1,310.55 ha. The changes in land cover which has a major influence on increasing surface temperature are built-up lands, open lands, and vegetation areas with an increase of 3 °C or 0.33 °C/year, while the land cover of water surfaces has increased in temperature by 2 °C or 0.22 °C/year. Those changes are inevitable because every region will continue to develop. However, several ways can be done to reduce the rate of change, such as conducting periodic checks and supervision on land cover changes, providing vegetation on built-up lands, especially settlements and commercial buildings and on water surfaces, also creating artificial water surfaces and irrigation in vegetation areas.